Modelagem do fator compensação "K" da equação de balanço de quantidade de movimento em banho metálico no LD - Willian dos Reis Lima (2021)
Through the momentum balance equation, the effectiveness of the blow in BOF reactors can be estimated. However, there is a term in this equation that is not considered by all scholars in this area, the compensation factor “K”. The complete domain of this factor and their application correctly promote reductions in process times and productivity gains. The present work aims at performing a study of the compensation factor "K" of the momentum balance equation in the metallic bath in the LD converters, for this a physical model test it was made. The similarity relations to characterize the metallic bath jet interaction, applying process variables essentials in oxygen blow step it has been considered. The results showed a configuration that has greater jet penetration has a smaller number nozzle number, greater airflow and smaller DBL. The nozzle number increase promoted the jet penetration decrease due to the increase of the injection point number keeping the critical diameter of the nozzle. The good influence of the tuyeres airflow in the jet penetration it was notice, as long as it does not occur jet collision between airflow of the lance and airflow of the tuyeres. The three-phase model where the oil layer was considered had smaller penetration compared to the two-phase model because the oil layer is a resistance element to be overcome by the air jet. Applying the penetrations got in three-phase and two-phase models in the newly developed equation, the “K” value was determined and showed smaller variations when was compared to the models. A comparison between “K” obtained in this study with that determined by MAIA (2016) showed a significant difference. The new development of the equation has been made through the cubic depressure method, who that enabled the evaluation of a single real root as an answer. The application of the method developed in the present work will lead to the reduction in the processing time and increase of productivity of BOF reactors.